REKASI PASAR TERHADAP KARAKTERISTIK PERUSAHAAN DAN KANTOR AKUNTAN PUBLIK - YOHANES FERNANDES; YULIUS KURNIA SUSANTO (Jurnal Bisnis dan Akuntansi, 2012)
The purpose of this study is to investigation over the influence of profitability, firm size, registered public accountant switch, auditor working period, audit opinion, reputation of registered public accountant against cumulative abnormal return. This study uses 65 samples of public manufacturing companies listed in Indonesia Stock Exchange from 2007 to 2010 which acquired using sampling purposive method, and obtained from annual report and audit report for each company. This study also use multiple regression analysis.The result of this research obtained that profitaibility and reputation of registered public accountant have a positive in influence cumulative abnormal return. While firm size, registered public accountant switch, auditor working period, and audit opinion have no impact on cumulative abnormal return.